Tariff Retaliation versus Financial Compensation in the Enforcement of International Trade Agreements - Limão, Nuno; Saggi, Kamal (World Bank, Washington, DC, 2012)
The authors analyze whether financial compensation is preferable to the current system of dispute settlement in the World Trade Organization that permits member countries to impose retaliatory tariffs in response to trade violations committed by other members. They show that monetary fines are more efficient than tariffs in terms of granting compensation to injured parties when there are violations in equilibrium. However, fines suffer from an enforcement problem since they must be paid by the violating country. If fines must ultimately be supported by the threat of retaliatory tariffs, they fail to yield a more cooperative outcome than the current system. The authors also consider the use of bonds as a means of settling disputes. If bonds can be posted with a third party, they do not have to be supported by retaliatory tariffs and can improve the negotiating position of countries that are too small to threaten tariff retaliation.